Presentation and Risk Factors of Ischaemic Stroke Patients (TAJ: Journal of Teachers Association, 2018)
Stroke is the third most common cause of death and is the main cause of neurological disability today. This is an observational study conducted at the department of Medicine, Rajshahi Medical College Hospital, Rajshahi, to observe the risk factors of ischaemic stroke and their presentation during hospital admission. Fifty patients of stroke with cerebral infarction confirmed by CT scan of brain were included. Hypertension (74%), diabetes (42%), overweight (22%), alcoholic (12%), past history of stroke (10%), previous history of TIA (16%), Carotid bruit (20%) and hypercholesterolemia (48%) were found as risk factors. Hemiplegia (96%), facial weakness (34%), deglutition problem (38%), speech difficulty (60%) and coma (14%) were observed during hospitalization.TAJ 2015; 28(2): 40-43